2011
DOI: 10.1007/s12562-011-0362-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR assay for the detection of the parasitic ciliate Cryptocaryon irritans

Abstract: We developed a quantitative PCR assay for detecting the parasitic ciliate Cryptocaryon irritans, which causes ''white spot disease'' in marine fishes, from the natural environment. A specific primer set for C. irritans was designed and its high specificity was confirmed in silico: almost all of the sequences deposited in the GenBank nucleotide database were covered, 22/23 for the forward primer and 7/7 for the reverse primer. We estimated that there were 3,415.9 rRNA gene copies per genome of C. irritans. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…This number may appear extremely elevated, in comparison to 1–15 copies found in bacteria [29], 30 copies found in marine stramenopiles MAST4 [24] and around 150 copies in Saccharomyces cerevisiae [30]. Yet, much higher numbers were reported in ciliates, ranging from 3415 in parasitic species Cryptocaryon irritans [31] to 160,000 copies in Vorticella sp. [32] and up to 200,000 in macronucleus of Stylonychia lemnae [33].…”
Section: Discussionmentioning
confidence: 88%
“…This number may appear extremely elevated, in comparison to 1–15 copies found in bacteria [29], 30 copies found in marine stramenopiles MAST4 [24] and around 150 copies in Saccharomyces cerevisiae [30]. Yet, much higher numbers were reported in ciliates, ranging from 3415 in parasitic species Cryptocaryon irritans [31] to 160,000 copies in Vorticella sp. [32] and up to 200,000 in macronucleus of Stylonychia lemnae [33].…”
Section: Discussionmentioning
confidence: 88%
“…For ciliates, the extremely high copy numbers of the rRNA gene might be one of the essential causes for polymorphism in this fragment (see also Gong et al 2013). Previous studies confirmed that ciliates generally host the highest rRNA gene copy number in a single cell than any other protist or fungi (Yao et al 1974;Prescott 1994;Heyse et al 2010;Taniguchi et al 2011;Gong et al 2013). In Vorticella sp., for example, around 300,000 SSU rRNA gene copies could be found in a single cell (Gong et al 2013).…”
Section: Origin Of Sequence Variationmentioning
confidence: 95%
“…The reported PCR (Chen et al 2008)-and qPCR (Taniguchi et al 2011)-based diagnostic methods developed for detection of C. irritans can only screen fish breeding waters suspected to contain C. irritans. When a parasite is absent or exists at low concentrations in the surrounding environment, these parasite-specific DNAbased diagnostic methods would not be able to detect the parasites in the water.…”
Section: Figurementioning
confidence: 99%
“…)‐ and qPCR (Taniguchi et al . )‐based diagnostic methods, which generally have higher sensitivity and specificity compared ELISA methods, have good potential in laboratory‐based epidemiology studies. However, use of PCR‐based methods in the open waters such as in mariculture will be impeded by lack of portable instrumentation and experienced personnel to conduct the test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation